Application of Mobile Learning in Aqidah Akhlak Subjects At MIN 1 Jombang - Machnunah Ani Zulfah; Amirotul Faiqoh (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
The application of mobile learning in MIN 1 Jombang aims to support learning to teach in the subject of Aqidah Ahklak and to know what are the factors that hinder and support in order to achieve maximum learning achievement. The formula of this research: 1) How is the application of mobile learning in the subject of Aqidah Akhlak in MIN 1 Jombang.? 2) What are the factors that hinder and population the application of Mobile Learning in the subject of Aqidah Akhlak in MIN 1 Jombang? This study aims to obtain answers to the application of mobile learning in MIN 1 Jombang and the factors that hinder and support this research is a qualitative research with a case study approach (case research). Data collection techniques use observation, interview, and documentation. Research data sources come from primary data, namely students and teachers, as well as secondary data such as print media and online media. Validity test using the source triangulation technique. Data analysis using domain analysis, taxonomy, compensatory, cultural themes. The application of Aqidah Akhlak learning in the pandemic period by using mobile learning media through several stages: planning and application, in its application is considered very good in the learning process in the pandemic period as today, while the inhibitory factors in this method are evaluated in the level of reasonableness and does not hinder the learning process . Meanwhile, the availability of free quota facilities for students and free wifi for teachers are very helpful for the smooth learning process of teaching and teaching moral beliefs in MIN 1 Jombang.